Pengaruh Variasitekanan Pengepresan Terhadap Karakteristik Pembakaran Briket Arang Daun Jati (Tectona Grandis L.F) - sarjono sarjono (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2019)
The potential of biomass teak leaves as an alternative source of energy is so abundant, but not yet fully realized. Teak leaf is one type of biomass that can be used as an alternative fuel. The objective of this research is to determine the influence of pressure variation on the combustion characteristics of teak biobriket charcoal. Testing carried out with a variation of pressing pressure of 350 psi, 600 psi, 850 psi, 1100 psi and 1350 psi.The test results of the influence of pressure variations on the presses against the combustion characteristics of teak charcoal briquettes show that biobriket with lower dipbriglutinous pressure has the highest combustion rate of 0.0928 grams/second. The combustion temperature rate reaches 486.4 ° C and the lowest temperature is 384.3 °c. Mass reduction will be quicker if the temperature of the air flowing into the fuel chamber is higher. The decrease in mass will be faster if airflow speed is raised. Low glutinous pressure causes the fuel to be shorter in its burning time.